Management of eight cases of subarachnoid hemorrhage using transpulmonary thermodilution during clazosentan therapy - Hiroto Iyota; Yasumasa Kawano; Hironori Fukumoto; Takato Tajiri; Mitsutoshi Iwaasa; Sinichi Morimoto; Yoshito Izutani; Shintaro Yamasaki; Kazuya Yamauchi; Hiroki Hatomoto; Hiroshi Abe; Yoshihiko Nakamura (Interdisciplinary Neurosurgery)
Clazosentan, an endothelin receptor antagonist, is used to prevent delayed neurological deterioration in patients with subarachnoid hemorrhage due to ruptured cerebral aneurysms. However, fluid management presents challenges. This single-center case series presents the findings from eight patients undergoing fluid management using transpulmonary thermodilution while receiving clazosentan. The median age of the patients was 49 years (interquartile range: 45.5–63.5), and four (50 %) were male. The median World Federation of Neurosurgical Societies classification was 5 (interquartile range: 2–5), and the median Fisher classification was 3 (interquartile range: 3). During clazosentan treatment, the median global end-diastolic volume index based on transpulmonary thermodilution remained at 715.5 ml/m2 (interquartile range: 643–788). No ischemic neurological deficits, bilateral pulmonary edema, and pleural effusion were observed. Strict fluid management using transpulmonary thermodilution might prevent the complications associated with clazosentan.